Mifepristone safety and efficacy in preinduction of labor: an observational study - Tejaswi, Thota Sai; Bidri, Shailaja R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: When the continuation of pregnancy adversely affecting the mother and fetus, termination of pregnancy is planned. Mifepristone as a method of pre-inducing agent in late pregnancy by increasing sensitivity of the uterus to the actions of prostaglandins and increasing uterine contractility. Objective of this study is to know the efficacy of mifepristone as a preinduction cervical ripening and induction of labor. Methods: In this prospective randomized study, 130 pregnant women are included and divided into two groups i.e. study group(n=65), has received tab mifepristone 200 mg and control group (n=65) has not received any drug. After the end of 24 hours, Bishops score in both the groups are assessed and those not in labor or with unfavourable cervix are administered with intracervical dinoprostone gel every 6 hourlies for maximum of 3 doses or until pregnant woman entered into active labor. Statistical analysis regarding improvement in Bishops score, induction active phase interval, induction delivery interval is observed. Results: After 24 hours, observation in the mean Bishops score has showed significant improvement in the study group (72.33%), when compared to control group (54.58%). % woman has gone into spontaneous labor in study group (61.5%), and in control group (75.4%). Induction to active phase time duration is less in study group with mean (10.53), and in control group (17.4). Induction to delivery time duration is also less in study group with mean (15.100) when compared to control group (22.100). 67.7% of patients has delivered by vaginally in study group, and in control group 41%. Conclusions: Tab. mifepristone 200 mg has a pre inducing agent for cervical ripening, shown better improvement in Bishops score within 24-48 hours and decreases time duration from induction to active phase and induction to delivery.